The Tenth Child in Folk Tradition Desetništvo v ljudskem izročilu - Kropej, Monika (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The tenth male (desetnik) or female child (desetnica), but also the ninth, the twelfth or the thirteenth child, have been preserved in the folk heritage of the Slavic, the Irish and the Baltic nations. The folk tradition of other nations contains several similarities in the stories abouth the seventh child of the same sex. Such a child is supposed to be a deity, a demonic creature, or a wizard. Researchers of folk epic and narrative tradition have discovered that Zeleni Jurij and Marjetica were marked as the tenth children as well. Zeleni Jurij is a deity which, according to folklore, brings renewal and fertility in spring, while his sister Marjetica is dedicated to the female counterpart of this deity. In folk songs the tenth son and the tenth daughter are either the tithe destined to the deities Perun and Mokoš, or else represent the two deities themselves.